CAUSES OF CRISIS SITUATION IN UKRAINE SUGAR INDUSTRY ENTERPRISES AND THEIR SOLUTIONS - G. Fyliuk; D. Sytenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Current state and major trends of functioning of the sugar industry enterprises in Ukraine are characterized. The industry's place in the structure of social production in Ukraine is highlighted. The dynamics of the number of operating sugar factories and dynamics of production and consumption of sugar in Ukraine during recent years are displayed. The performance of the sugar factories is analyzed. Forecasted assessment of the of PEST- factors on the development of the sugar industry is shown. The basic entry barriers to the industry for new players are indicated. The description of major players in the sugar market is made. Level of concentration of sugar market in Ukraine is calculated and conclusions about its dynamics are made. Factors of crisis state of sugar industry enterprises in Ukraine are determined. Suggestions on implementation of priority measures aimed at improving the efficiency of industry's management in order to drive the enterprises out of the crisis are formulated.